The main barriers of Portuguese entrepreneurship ecosystem: Interpretive Structural Modeling (ISM) approach - Banha, F; Almeida, H; Rebelo, E.; Orgambídez-Ramos, A. (Tourism & Management Studies)
This study is based on the technique Interpretive Structural Modelling (ISM), in order to delineate a flowchart that shows the main ten barriers (and their relationships) influencing the development of Portuguese Entrepreneurship Ecosystem. Through a process of modelling it was possible to reach a graphical representation that shows the operating sequence of these barriers in order to understand the logic of their relationship. The results show a model represented by a flowchart consisting of 10 barriers, three of them that are positioned at the base of the model have political-legislative features with high level of range in all the remaining barriers, so a political involvement, carefully measured, could contribute to the improvement of the Portuguese Entrepreneurship Ecosystem. The final model is a useful tool that can be adopted by key decisionmakers and players in the Ecosystem in order to optimize the selection of measures enabling the entrepreneurial activity in Portugal.